Gender, nationalism, and genocide in Bangladesh : Naristhan/Ladyland - Rashid, Azra (New York: Routledge, 2019)
"The 1971 genocide in Bangladesh took place as a result of the region's long history of colonization, the 1947 partition of the Indian subcontinent into largely Muslim Pakistan and Hindu India, and the continuation of ethnic and religious politics in Pakistan, specifically the political suppression of the Bengali people of East Pakistan. The violence endured by women during the 1971 genocide is repeated in the writing of national history. The secondary position that women occupy within nationalism is mirrored in the nationalist narratives of history. This book engages with the existing feminist scholarship on gender, nationalism and genocide to investigate the dominant representations of gender in the 1971 genocide in Bangladesh and juxtaposes the testimonies of survivors and national memory of that war to create a shift of perspective that demands a breaking of silence. The author explores and challenges how gender has operated in service of Bangladeshi nationalist ideology, in particular as it is represented at the Liberation War Museum. The archive of this museum in Bangladesh is viewed as a site of institutionalized dialogue between the 1971 genocide and the national memory of that event. An examination of the archive serves as an opening point into the ideologies that have sanctioned a particular authoring of history, which is written from a patriarchal perspective and insists on restricting women's trauma to the time of war. To question the archive is to question the authority and power that is inscribed in the archive itself and that is the function performed by testimonies in this book"--
Historical background -- Gender, nationalism and genocide -- Archives, museums and the politics of representation -- Stories of resistance.
Includes bibliographical references and index.
Keywords: Women -- Bangladesh; Women -- Bangladesh; Nationalism -- Bangladesh